Population Growth, Dependency, and Consumption - Weil, David N (American Economic Review, 1999)
This paper examines how population growth affects the average level of utility particularly the consumption per capita. It also focuses on the effects of population growth on the ratio of dependent consumers to working-age adults. The model employed in this paper has three demographic groups: working-age adults who produce and consume and the young and elderly who only consume. This study concluded that the transition to lower population growth requires a long period of reduced dependency in which society benefits from lower spending on children while it has yet to pay for higher old-age dependency. The dependency level after 30 years is not significantly different from that which would exist in an optimal stable population. Any rise in fertility that would decrease old-age dependency in the long run would require a lengthy period of higher-than-steady-state dependency.